ALOE ECELL: A STUDY ON USING ALOE VERAIN ECO-FRIENDLYBATTERIES (International Journal of Food and Nutritional Sciences, 2022)
"Going Green with Aloe Vera Batteries: A Sustainable Solution for Our Energy Needs?" E-waste is the fastest-growing waste in the twenty-first century. Dry cell batteries are quickly filling landfills. This small dead battery causes toxic heavy metals to leach into ground water, soil, and the surface, causing pollution. It also has the potential to cause leaching into agricultural fields. As a result, a multifaceted problem arises. Aloe Vera batteries have been identified as a promising solution to the dangers posed by disposable dry cells. This research paper aims to know whether people are aware of the chemicals used in traditional batteries, and their acceptance of Aloe Vera as a material for battery production, with a focus on its environmental impact and potential to replace synthetic materials. This paper discusses Aloe Vera batteries and highlights their potential benefits, but also mentions some challenges that need to be overcome.